FAMILY HEALTH SUPPORT CENTER: AN INTERSECTION BETWEEN PRIMARY AND SECONDARY HEALTH CARE - Carine Vendruscolo (Texto & Contexto Enfermagem, 2019)
Objective: to identify the space in which the Family Health Support Center is structured in the services and how it works within the scope of the Unified Health System. Method: a conceptual study based on partial results of a multicenter, descriptive-exploratory study with a qualitative approach, carried out in 2017, in the State of Santa Catarina, with managers and professionals from the Family Health Support Center. Content thematic analysis was used with the data from semi-structured interviews with professionals and individual interviews with managers, totalling 18 participants. Results: the professionals of the Family Health Support Center are identified as specialists who work in or close interaction with Primary Health Care, in the context of matrix support, in order to assist in the planning of the Health Care Network, which strengthens the general practice in Family Health. In addition to primary health care, they can act in intercessory spaces and perform secondary health care; set forth possibilities for intervention and enhance inter-sectoriality and co-responsibility. Conclusion: the Family Health Support Center was recognized as an important articulator of interdisciplinarity in health work, cabable of promoting comprehensive and intersectoral care, in addition to its initial proposal of supporting the Family Health Strategy, which could help in the coordination and fulfillment of secondary health care in the Brazilian Unified Health Care System, thus being an intersecting space between primary and secondary health care.